Kualitas Pelayanan Pemeriksaan Sanitasi Kapal Di Kantor Kesehatan Pelabuhan Kelas II Dumai - Dianis, Rahma; Heriyanto, Meyzi; Mayarni, Mayarni; Anjani, Nurul (Peneliti.net, 2024)
This research is motivated by the fact that the ship sanitation inspection service carried out by the Dumai Class II port service office is quite easy and simple for ship crews to carry out inspections in accordance with the established SOP. This is what makes the number of publications SSCEC/SSCC certificates and Health Book documents will increase rapidly in 2022.The aim of this research is to determine the quality of service, obstacles and efforts to implement ship sanitation inspections at Dumai Class II KKP. The method used in this research is a qualitative approachwith the data collection process through observation, interviews and documentation. This research also uses triangulation of data sourced from officers and service users of the Dumai KKP. Based on the research results it was found that 1)tangible quality, the KKP has provided a new building that is comfortable for users with the appearance of the officers according to applicable standards, however the service is still not optimal due to unsupported inspection equipment. 2) realiable quality, the KKP has made a picket schedule to maximize service, however, officers are still unable to complete the service according to the SOP. 3) responsiveness quality, namely officers are responsive in serving users. 4) quality of competence, officers have good knowledge and skills in providing services. 5) courtesy quality where officers are able to be kind and friendly in providing services. 6) quality of credibility, officers do not perform services outside the applicable SOP. 7) quality of security, KKP provides guaranteed security and comfort for service users. 8) quality of access, service users can access because services can be provided online. 9) quality of communication, there is good communication so that users are willing to follow directions from officers. 10) quality of understanding the customer, officers can understand service users. Apart from that, there are inhibiting factors in the quality of services provided due to lack of human resources/officers, lack of facilities and infrastructure and the responsiveness of officers. The efforts made by the KKP include adding facilities, adding officers and improving the performance of officers in serving service users at the Dumai KKP.